Predictive Value of Middle Cerebral Artery to Uterine Artery Pulsatility Index Ratio in Hypertensive Disorders of Pregnancy - Prashanth Adiga; Indumathi Kantharaja; Shripad Hebbar; Lavanya Rai; Shyamala Guruvare; Anjali Mundkur (Hindawi Limited, 2015)
Aims and Objectives. (i) To determine the predictive value of cerebrouterine (CU) ratio (middle cerebral artery to uterine artery pulsatility index, MCA/UT PI) in assessing perinatal outcome among hypertensive disorders of pregnancy. (ii) To compare between CU ratio and CP ratio (MCA/Umbilical artery PI) as a predictor of adverse perinatal outcome. Methods. A prospective observational study was done in a tertiary medical college hospital, from September 2012 to August 2013. One hundred singleton pregnancies complicated by hypertension peculiar to pregnancy were enrolled. Both CU and CP ratios were estimated. The perinatal outcomes were studied. Results. Both cerebrouterine and cerebroplacental ratios had a better negative predictive value in predicting adverse perinatal outcome. However, both CU and CP ratios when applied together were able to predict adverse outcomes better than individual ratios. The sensitivity, specificity, positive predictive value, and the negative predictive values for an adverse neonatal outcome with CU ratio were 61.3%, 70.3%, 56%, and 78.9%, respectively, compared to 42%, 57.5%, 62%, and 76% as with CP ratio. Conclusion. Cerebrouterine ratio and cerebroplacental ratio were complementary to each other in predicting the adverse perinatal outcomes. Individually, both ratios were reassuring for favorable perinatal outcome with high negative predictive value.